Comparaison ecologique de la vallee du rift ethiopien et d'autres regions d'Afrique - Russell-Smith, A. (1984)
Compares the climates and soils and vegetation of the Ethiopian Rift Vallety with those of other areas in Africa, with particular reference to the screening of forage species. Examines the diversity of climates and soil conditions as they constitute constraints to forage or crop production in the Rift Valley, classifying major tribes in the grass flora, & analysing the adaptability of some genera of tropical forage legumes in commercial use to water stress, heat stress & poor soil.